Changes in structural brain development after selective fetal growth restriction in monochorionic twins. (1st June 2022) - Groene, S. G.; de Vries, L. S.; Slaghekke, F.; Haak, M. C.; Heijmans, B. T.; de Bruin, C.; Roest, A. A. W.; Lopriore, E.; van Klink, J. M. M.; Steggerda, S. J.
Abstract: Objectives: Fetal growth restriction (FGR) may alter brain development permanently, resulting in lifelong structural and functional changes. However, in studies addressing this research question, FGR singletons have been compared primarily to matched appropriately grown singletons, a design which is inherently biased by differences in genetic and maternal factors. To overcome these limitations, we conducted a within‐pair comparison of neonatal structural cerebral ultrasound measurements in monochorionic twin pairs with selective FGR (sFGR). Methods: Structural cerebral measurements on neonatal cerebral ultrasound were compared between the smaller and larger twins of monochorionic twin pairs with sFGR, defined as a birth‐weight discordance (BWD) ≥ 20%, born in our center between 2010 and 2020. Measurements from each twin pair were also compared with those of an appropriately grown singleton, matched according to sex and gestational age at birth. Results: Included were 58 twin pairs with sFGR, with a median gestational age at birth of 31.7 (interquartile range, 29.9–33.8) weeks and a median birth weight of 1155 g for the smaller twin and 1725 g for the larger twin (median BWD, 32%). Compared with both the larger twin and the singleton, the smaller twin had significantly smaller cerebral structures (corpus callosum, vermis, cerebellum), less white/deep gray matter and smaller intracranial surface area and volume. Intracranial‐volume discordance and BWD correlated significantly ( R 2 = 0.228, P < 0.0001). The median intracranial‐volume discordance was smaller than the median BWD (19% vs 32%, P < 0.0001). After correction for intracranial volume, only one of the observed differences (biparietal diameter) remained significant for the smaller twin vs both the larger twin and the singleton. Conclusions: In monochorionic twins with sFGR, neonatal cerebral ultrasound reveals an overall, proportional restriction in brain growth, with smaller cerebral structures, less white/deep gray matter and smaller overall brain‐size parameters in the smaller twin. There was a positive linear relationship between BWD and intracranial‐volume discordance, with intracranial‐volume discordance being smaller than BWD. © 2021 The Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of International Society of Ultrasound in Obstetrics and Gynecology.